The role of probiotics in the prevention and treatment of diseases - Байгужина, Ж.С.; Хасенова, А.Е.; Елеупаева, Ш.К.; Динмухамедова, А.С.; Альжанова, Г.С.; Айзман, Р.И.; Базарбаева, С.М.; Хамзина, С.Р. (Fundamental and Experimental Biology, 2023)
Probiotics, including bacteria and yeast, are living microorganisms that have a beneficial effect on human health. Some of these microorganisms form part of the normal human gut microbiota, where they live in a symbiotic relationship. Recently, probiotic microorganisms are constantly being studied and their use is being considered in promising methods of prevention and treatment of various diseases. Clinical trials and experiments in vitro, in vivo have expanded the current understanding of the important role that probiotics play in diseases related to the human gut microbiome. Many studies have noted that probiotics are involved in the formation of the intestinal microbiota, which leads to the potential control of multiple intestinal diseases and promotes overall wellness. Convincing evidence in favor of the use of probiotics are such diseases associated with the intestinal microbiome as antibiotic-associated diarrhea, chronic constipation, irritable bowel syndrome, colorectal cancer and various disorders of the gastrointestinal tract. Probiotics are also used for the treatment and prevention of diseases not related to the gastrointestinal tract, such as atopic dermatitis, allergies, cardiovascular diseases, urogenital infections and cancers. However, in these cases, the exact mechanisms of action of probiotics are insufficiently studied and further research in this direction is required. The purpose of this article is to provide the latest information on the use of probiotics in the prevention and treatment of various diseases.